1978
DOI: 10.1055/s-0038-1648642
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and Risk Factors in Deep Vein Thrombosis

Abstract: SummaryThe incidence of deep vein thrombosis (DVT) as diagnosed by the 125I fibrinogen test (125IFT) was determined in a series of 300 newly admitted medical and 201 surgical patients. 6 medical patients died before 125IFT screening could be completed. The incidence of DVT was l4% in medical patients and 18% in surgical patients. Increasing age, a malignant condition and a past history of thromboembolism all increased the risk of DVT. Increasing levels of cigarette smoking were found to be associated with a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

1980
1980
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 4 publications
3
18
0
Order By: Relevance
“…In addition to these inherent challenges, the chronicity of alcohol use and the association of alcohol use with other comorbid conditions and lifestyle choices (e.g. cigarette smoking) that are associated with DVT is unknown [34]. It indeed seems possible, and perhaps even likely, that the viscoelastic properties of an acutely intoxicated patient differ significantly from those of a chronic alcohol user.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these inherent challenges, the chronicity of alcohol use and the association of alcohol use with other comorbid conditions and lifestyle choices (e.g. cigarette smoking) that are associated with DVT is unknown [34]. It indeed seems possible, and perhaps even likely, that the viscoelastic properties of an acutely intoxicated patient differ significantly from those of a chronic alcohol user.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that it has been claimed paradoxically that smoking protects against thromboembolic complications after myocardial infarction, 5051 and also protects against the development of deep venous thrombosis. 52 ' a In these situations, the lowered levels of factor VIII R:Ag may be more important than the accompanying reduction in fibrinolytic activity.…”
Section: Discussionmentioning
confidence: 99%
“…32 In comparison, Prescott et al reported that rising levels of cigarette smoking were associated with a lower incidence of DVT. 33 TB was found to be common among the patients with diagnosed DVT at 12.4%. Robson et al demonstrated that DVT caused by TB is most probably due to the increase in plasma fibrinogen with impaired fibrinolysis and a decrease in anti-thrombin III.…”
Section: Hiv Prevalencementioning
confidence: 93%